Serological evidence for transmission of multiple dengue virus serotypes in Papua New Guinea and West Papua prior to 1963 - Luang-Suarkia, D.; Ernst, T.; Alpers, Michael Philip; Garruto, R.; Smith, D.; Imrie, A. (Public Library of Science, 2017)
Little is known about the natural history of dengue in Papua New Guinea (PNG). We assessed dengue virus (DENV)-specific neutralizing antibody profiles in serum samples collected from northern and southern coastal areas and the highland region of New Guinea between 1959 and 1963. Neutralizing antibodies were demonstrated in sera from the northern coast of New Guinea: from Sabron in Dutch New Guinea (now known as West Papua) and from four villages in East Sepik in what is now PNG. Previous monotypic infection with DENV-1, DENV-2, and DENV-4 was identified, with a predominance of anti-DENV-2 neutralizing antibody. The majority of positive sera demonstrated evidence of multiple previous DENV infections and neutralizing activity against all four serotypes was detected, with anti-DENV-2 responses being most frequent and of greatest magnitude. No evidence of previous DENV infection was identified in the Asmat villages of the southern coast and a single anti-DENV-positive sample was identified in the Eastern Highlands of PNG. These findings indicate that multiple DENV serotypes circulated along the northern coast of New Guinea at different times in the decades prior to 1963 and support the notion that dengue has been a significant yet neglected tropical infection in PNG for many decades.